Intelligent vertical handoff decision strategy based on network performance prediction and consumer surplus value for next generation wireless networks. Issue 4 (1st July 2017) - Cheelu, Dhanaraj; Madda, Rajasekhara Babu; Chen, Chi‐Yuan; Venkata Krishna, P.; Yenduri, Sumanth
Abstract : Vertical handoff (VHO) decision services play an essential role in the current wireless networks. Many algorithms designed aim at quality of service while granting seamless roaming amongst a number of heterogeneous access networks. In this study, the authors proposed an intelligent VHO decision strategy targeting to maximise user satisfaction without compromising on quality of service for non‐real time mobile based services. The proposed strategy applies consumer surplus value (CSV)‐based pricing scheme and also a prediction system to approximate network performances at various intervals. Finally, a fuzzy rule‐based behavioral system is proposed to find optimal network by considering both CSV as well as network performance as stimulus parameters. Simulation is carried out using OM Net++ and MATLAB, and the results are acknowledged with discussion and analysis.